Perceived Social Support Partially Mediates the Impact of Temperament and Character on Postpartum Depression - Nakamura, Yukako; Takahashi, Nagahide; Yamauchi, Aya; Morikawa, Mako; Okada, Takashi; Ozaki, Norio (Frontiers in Psychiatry, 2022)
Introduction Temperament and character of pregnant women, especially harm avoidance and self-directedness have been identified as risk factors for postpartum depression, in addition to poor social support. However, the relationship between these personality traits and social support for depressive symptoms after delivery has not been examined. Methods Data were extracted from a prospective cohort survey on pregnant women conducted in Nagoya, Japan that included the Temperament and Character Inventory, the Social Support Questionnaire, and the Edinburgh Postnatal Depression Scale at approximately week 25 and 1 month postpartum. A mediation analysis using structural equation modeling was used to test if social support in pregnancy is a mediator between personality traits and postpartum depressive symptoms. Results 1,559 women were included in the analysis. Both harm avoidance and self-directedness were significantly associated with depressive symptoms (total effect: β [SE], 0.298 [0.041], P <0.001 for harm avoidance; total effect: β [SE], -0.265 [0.067], P <0.001 for self-directedness). Mediation analysis showed that the effect of harm avoidance on depressive symptoms was partially mediated by low social support (direct effect: β [SE], 0.193 [0.004], P <0.001; indirect effect: β [SE], 0.082 [0.034], P =0.015). Self-directedness on depressive symptoms was not found to be mediated by low social support. Conclusion Results indicate that poor social support worsens depressive symptoms in women with high HA during pregnancy. Limitations include a possible selection bias due to the limited target facilities; most variables being evaluated based on self-report questionnaires, and different number of samples available for analysis between harm avoidance and self-directedness.